Solid clues : - Feinberg, Gerald (Simon and Schuster, 1985)
Part one: The State of the Art: What we know now; Part two: At the Threshold of Understanding posing new questions; Part three: A fertile borrowing: Ourside influences on science; Part four: Science in the twety-first Century Part three: A fertile borrowing: Outside influences on science Part four: Science in the Twenty-first century